Simulation of the Flat-parallel Movement of a Bridge Agricultural Unit with an Articulated Frame - Bulgakov, V.; Ivanovs, S.; Volskyi, V.; Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич (My University, 2020)
The work presents foundations of the dynamics of the flat-parallel movement of a bridge agricultural unit in a horizontal with the kinematic method of its control (turning the wheels) by changing the position of one of its parts relative to the other. The analysis of assessment of the degree of impact of the scheme and parameters of the investigated agricultural tool upon its controllability and stability of movement is based on the amplitude and phase frequency characteristics. The mathematical models of the movement of the bridge agricultural unit are presented in a differential and an operator form of recording. Based on mathematical models, the calculated amplitude and phase frequency characteristics of the dynamic control system of the control impact, presented as the angular displacement of its half-frames ψ, are constructed for various parameters and operating modes. The constructed mathematical models, amplitude and phase frequency characteristics make it possible to assess the impact of the control parameter of the bridge agricultural unit, as well as its design and other parameters upon the controllability of the movement.
Keywords: farming; wide span tractor; pivot; frame; turning; mathematical modelling